الحكمة العلمية في تحريم لحم الميتة والخنزير والجوارح - فوزي، عثمان Fawzi, Othman; عبدالوهاب، صفا عبدالسلام Abdulwahab, Safa Abdulsalam; الجبورى، محمد خلف صالح حلو (جامعة تكريت - كلية التربية للعلوم الإنسانية, 2018)
Praise be to Allah, Lord of the Worlds, and prayers and peace be upon the envoy, mercy to the worlds Muhammad in front of the prophets and messengers, and on his family and his good companions . In this study, which is entitled "The Scientific Wisdom of the Prohibition of the Meat of the Dead, the Pig and the Carpenters", this is an important subject in Islamic law. Islam has taken care of human food with great concern and has taken care of all its details and particulars . And among the forbidden foods harmful to the flesh of the dead and pork and meat of prey, which is the search for a statement of its impact on everyone who deals with it, and a statement of the approval of the modern science of the Koran and Sunnah laws purified by 1439 years, The importance of the subject is to show the greatness of the Islamic religion by stating that all that came in modern science does not deviate from what was stated in the Koran and the Sunnah of legislation, which is the prohibition of dead and pork and meat, one of them, which has a great impact in defense and lament what attributed to Two of the enemies of religion, causing to enter the suspicion of a number of Muslims who Bta their religion influenced by others, and has a great impact in persuading non-Muslims and invite them to ratify and faith as brought by Islam, as well as its importance in enhancing the confidence of Muslims to their religion and the great Islamic law. I have divided my research into three demands. The first requirement is: dead, evidence of its prohibition, and scientific wisdom in its prohibition. As for the second requirement: it was about pork, evidence of its prohibition, scientific wisdom in its prohibition, and finally the third requirement: And I concluded my research with a conclusion that included the most important conclusions I reached through my studies, followed by margins, sources and references, and a summary in Arabic and English. In conclusion, I ask God to accept this work, and forgive for what happened in the shortness or slippage. And our last prayer is that the Praise be to Allah, Lord of the Worlds, and prayers and peace be upon the Seal of the Prophets and Messengers Muhammad, his family and companions and those who followed Him with charity until the Day of Judgment.
الحمد لله رب العالمين، والصلاة والسلام على المبعوث رحمة للعالمين محمد أمام الأنبياء والمرسلين، وعلى آله وصحبه الطيبين الطاهرين. أما بعد: فأحمد الله تعالى الذي وفقني في اختيار موضوع هذا البحث، والذي يحمل عفوان (الحكمة العلمية في تحريم لحم الميتة والخنزير والجوارح)، هذا الموضوع المهم في الشريعة الإسلامي، فقد اهتم الإسلام بطعام الإنسان اهتماما بالغا، واعتنى بكل تفصيلاته وجزئياته. فأحل الله تعالى من الأطعمة أطيبها وأنفعها، وحرم الخبيث الضار منها، ومن جملة الأطعمة المحرمة الضارة لحم الميتة والخنزير ولحوم الجوارح، والتي يدور عنها البحث بيانا لمضارها على كل من يتناولها، وبيانا لموافقة العلم الحديث لتشريعات القرآن الكريم والسنة النبوية المطهرة من قبل ١٤٣٩ سنة، فتتمثل أهمية الموضوع بإظهار عظمة الدين الإسلامي عن طريق بيان أن كل ما جاء به العلم الحديث لا يحيد عما جاء في القرآن الكريم والسنة النبوية من تشريعات والتي يعد تحريم الميتة والخنزير ولحوم الجوارح أحدها، مما له الأثر العظيم في الدفاع والذب عما نسب إليهما من أعداء الدين مسببا لدخول الشك لدى عدد من المسلمين الذين بعدوا عن دينهم تأثر بالآخرين، كما له الأثر العظيم في إقناع غير المسلمين ودعوتهم للتصديق والإيمان بما جاء به الإسلام، فضلا عن أهميته في تعزيز ثقة المسلمين بدينهم وشريعتهم العظيمة وقد قسمت بحثي إلى ثلاثة مطالب، حيث جاء في المطلب الأول: الميتة، وأدلة تحريمها، والحكمة العلمية في تحريمها، وأما المطلب الثاني: فقد كان عن الخنزير، وأدلة تحريمه، والحكمة العلمية في تحريمه، وأخيرا المطلب الثالث: وكان عن لحوم الجوارح، وأدلة تحريمها والحكمة العلمية في تحريمها، واختتمت بحثي بخاتمة تضمن أهم النتائج التي توصلت إليها من خلال دراستي، وتليه الهوامش والمصادر والمرجع ثم ملخص بالعربية والإنكليزية. وفي الختام أسال الله تعالى أن يتقبل الله هذا العمل، ويعفو عن ما وقع فيه من تقصير أو زلل. وآخر دعوانا أن الحمد لله رب العالمين، والصلاة والسلام على خاتم الأنبياء والمرسلين محهد وعلى آله وصحبه ومن تبعه بإحسان إلى يوم الدين.
Keywords: الأطعمة والأشربة -- الحظر والإباحة -- المسائل الفقهية -- الأحكام الشرعية